The Tiger - Park Hoon-jung; Lee Mogae; Choi Min-sik; Jeong Man-sik; Kim Hong-pa (Eureka Video, 2017)
Following a tragic accident involving the loss of his beloved wife, renowned hunter Man-duk has retired his rifle and become a humble herb gatherer limping amongst his cherished mountains with his son. But with the arrival of Japanese soldiers determined to find a legendary great tiger, Man-duk finds himself pulled into one final hunt for his own personal redemption and closure. Set during the Japanese occupation of Korea, a period when Korean tigers are being hunted to extinction, "The Tiger" is a breathtaking action adventure from one of Korea's finest writer-directors, Park Hoon-jung. [Cover]